Synthesis of Well-Dispersed TiO2 Nanoparticles by a Sol-Hydrothermal Method - Xu1, Haiyan; Song2, Zhiqiang; Wang3, Xudong; Wang2, Hao (Asian Journal of Chemistry, 2011)
Phase pure anatase TiO2 nanoparticles have been synthesized using a simple sol-hydrothermal method. The products were characterized by X-ray diffraction, Raman spectroscopy, transmission electron microscopy and ultraviolet-visible spectroscopy. The results showed that the TiO2 particles were well-dispersed and the average size was limited in the range of 10 nm. The optical measurement displayed the obvious quantum-size effect of the products.